Pseudo-Subarachnoid Hemorrhage Found in Patients with Postresuscitation Encephalopathy: Characteristics of CT Findings and Clinical Importance - Yuzawa, H.; Higano, S.; Mugikura, S.; Umetsu, A.; Murata, T.; Nakagawa, A.; Koyama, A.; Takahashi, S. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: High-attenuation areas (HDAs) called pseudo-subarachnoid hemorrhages (SAHs) may develop in some patients resuscitated from cardiopulmonary arrest (CPA), though no hemorrhage has occurred. We investigated the imaging characteristics and clinical significance of this phenomenon.MATERIALS AND METHODS: CT images of consecutive patients resuscitated from nontraumatic CPA were reviewed and classified into cases with pseudo-SAH (pseudo-SAH[+] group, n = 9), those without pseudo-SAH (pseudo-SAH[−] group, n = 28), and those with true SAH (SAH-CPA group, n = 8). Typical patients with SAH (SAH group, n = 13) and 20 healthy individuals were also extracted as control groups. The degree of brain edema was scored visually as none, mild, or severe, and the CT values of the HDAs and brain parenchyma were measured. These parameters were compared among the groups. We also compared the prognosis between the pseudo-SAH(+) and pseudo-SAH(−) groups.RESULTS: On CT, pseudo-SAH was associated with severe brain edema, whereas there was mild or no edema without pseudo-SAH. The CT values of the HDAs in the pseudo-SAH(+) group were significantly lower than those of the CPA-SAH and SAH groups (P < .0001). The brain parenchyma of the pseudo-SAH(+) group had the lowest CT values among all of the groups (P < .0001). The prognosis of the pseudo-SAH(+) group was significantly poorer than that of the pseudo-SAH(−) group in terms of both clinical outcome (P = .02) and survival (P = .046).CONCLUSION: The findings of pseudo-SAH have several imaging characteristics differing from SAH and predict a poor prognosis. This provides important information that can be used for deciding treatment strategies.